2017
DOI: 10.1007/s00280-017-3293-x
|View full text |Cite
|
Sign up to set email alerts
|

Computed determination of the in vitro optimal chemocombinations of sphaeropsidin A with chemotherapeutic agents to combat melanomas

Abstract: The use of a response surface model offers the possibility of reducing the experiments while determining accurately the optimal combinations. We herein highlighted that combining the Na/K/2Cl cotransporter and/or anion exchanger inhibitor Sph A with chemotherapeutic agents could improve the therapeutic benefits of conventional chemotherapies against advanced melanomas, particularly because Sph A exerts cytotoxic effects regardless of the genetic BRAF and NRAS status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…92 The authors found that 75 μM of cisplatin and 850 μM of temozolamide (DNA damaging agents) combined with 4 to 6 μM of sphaeropsidin A provided the maximum in vitro cytotoxic response with >90% of cellular lethality. 92 The authors found that 75 μM of cisplatin and 850 μM of temozolamide (DNA damaging agents) combined with 4 to 6 μM of sphaeropsidin A provided the maximum in vitro cytotoxic response with >90% of cellular lethality.…”
Section: Icacina Trichanthamentioning
confidence: 99%
See 1 more Smart Citation
“…92 The authors found that 75 μM of cisplatin and 850 μM of temozolamide (DNA damaging agents) combined with 4 to 6 μM of sphaeropsidin A provided the maximum in vitro cytotoxic response with >90% of cellular lethality. 92 The authors found that 75 μM of cisplatin and 850 μM of temozolamide (DNA damaging agents) combined with 4 to 6 μM of sphaeropsidin A provided the maximum in vitro cytotoxic response with >90% of cellular lethality.…”
Section: Icacina Trichanthamentioning
confidence: 99%
“…Furthermore, a very recent 2017 article describes a positive synergistic effect of sphaeropsidin A with cisplatin and temozolamide against the predictive kinase biomarkers for the melanoma tumors serine/threonine protein kinase B-raf, mitogen activated protein kinase, and a receptor tyrosine kinase, to increase their vitro efficiency. 92 The authors found that 75 μM of cisplatin and 850 μM of temozolamide (DNA damaging agents) combined with 4 to 6 μM of sphaeropsidin A provided the maximum in vitro cytotoxic response with >90% of cellular lethality. This combination chemotherapy with different mechanisms of action (ion transport inhibitor with DNA damaging agents) could lead to a lower therapeutic dose of these cytotoxic anticancer agents with reduced side effects.…”
Section: Icacina Trichanthamentioning
confidence: 99%
“…Compound 20 exhibited in vitro antibacterial activity towards Xanthomonas oryzae pv. oryzae , the causal agent of rice bacterial blight [ 43 ] and showed promising anticancer activity against drug-resistant melanoma cells [ 44 , 45 ]. Given that the absolute configuration (AC) is strictly linked to biological activity [ 46 , 47 ], the AC of 12 – 14 , 19 and 20 was determined using different methods [ 48 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…In vitro combinations of sphaeropsidin A (Sph A) (66) with either cisplatin or temozolomide, showed that combining 4 µM Sph A with 75 µM cisplatin for 72 h had a synergistic cytotoxic effect independent of BRAF or NRAS mutations [96].…”
Section: Combination Therapiesmentioning
confidence: 99%